1997
DOI: 10.1074/jbc.272.14.9147
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a Novel, Membrane-bound, 80-kDa Matrix-degrading Protease from Human Breast Cancer Cells

Abstract: A major, apparently novel extracellular matrix-degrading protease was previously identified and partially isolated from hormone-dependent but not from hormone-independent human breast cancer cells (Shi, Y. E., Torri, J., Yieh, L., Wellstein, A., Lippman, M. E., and Dickson, R. B. (1993) Cancer Res. 53, 1409 -1415). Although initially the 80-kDa protease was identified from breast cancer cell-conditioned medium, immunofluorescence staining of breast cancer cells with anti-80-kDa protease monoclonal antibody 21-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
113
1
1

Year Published

1999
1999
2018
2018

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 119 publications
(117 citation statements)
references
References 32 publications
2
113
1
1
Order By: Relevance
“…Purification of Matriptase from Human Milk-In our previous study (7), a small proportion of the matriptase molecules were identified as complexes in human breast cancer cells. We have subsequently found human milk to be a good source for isolation of larger quantities of the matriptase complexes (39).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Purification of Matriptase from Human Milk-In our previous study (7), a small proportion of the matriptase molecules were identified as complexes in human breast cancer cells. We have subsequently found human milk to be a good source for isolation of larger quantities of the matriptase complexes (39).…”
Section: Resultsmentioning
confidence: 99%
“…Immunoblot Analysis-Immunoblotting was conducted as described previously (7). Proteins were separated by 10% SDS-polyacrylamide gel electrophoresis, transferred to polyvinylidene fluoride membrane, and subsequently probed with anti-matriptase mAb 1 M32.…”
Section: Expression Of Snc19 In Cos-7mentioning
confidence: 99%
See 1 more Smart Citation
“…Matriptase is known as an integral membrane protein that is localized at the plasma membrane, however, as we have shown before, the majority of matriptase resides inside the cell (18,35). This intracellular pool of matriptase is anchored to the intracellular membranes surrounding the nucleus, and is the pool of enzyme that is assayed in the in vitro, cell-free activation system (16).…”
Section: Intracellular Acidification and Matriptase Activation-mentioning
confidence: 99%
“…HAI-1 was also identified from human breast milk in a complex with another serine protease, named matriptase (10). Matriptase is an epithelial cell-derived serine protease that has extracellular matrix-degrading activity and has been proposed to play a role in breast cancer invasion (11,12). Thus, HAI-1 may also function as a regulator of tumor progression by controlling the activity of an extracellular matrix-degrading enzyme.…”
mentioning
confidence: 99%